OPEnS Hub: Real-Time Data Logging, Connecting Field Sensors to Google Sheets - DeBell, Thomas; Goertzen, Luke; Larson, Lars; Selbie, William; Selker, John; Udell, Chet (Frontiers in Earth Science, 2019)
In Earth science, we must often collect data from sensors installed in remote locations. Retrieving and storing these data can be challenging. Present options include proprietary commercial dataloggers, communication devices, and protocols with rigid software and data structures that may require ongoing expenses. While there are open-source solutions that include telemetry, such as EnviroDIY’s Mayfly, none presently generate real-time, remotely accessible workbooks. The OPEnS Lab developed the OPEnS Hub, a new approach to using low-power, open-source hardware and software to achieve real-time data logging from the field to the web. The Hub is an order of magnitude less expensive than commercial products, inherently modular and flexible, and aims to reduce technical barriers for users with little programming experience. Data can be collected remotely using a host of transmission protocols to relay data from distributed in-situ monitoring devices. The Hub mesh-networks with several nodes and saves to an onboard microSD card. Telemetry options include 900 MHz Long Range Radio with up to 25 km range and nRF for higher data rates. Ongoing transmissions from the Hub to the internet currently employ Ethernet with potential support for Wi-Fi and the cell network. The Hub engages a dynamic, low-latency portal to Google Sheets via the free API, PushingBox, and an adaptable Google Apps Script. This framework was tested on 12 individual sensors nodes at remote sites in Oregon. This manuscript details our methods and evaluates PushingBox, Google Apps Script, Adafruit Industries’ open-hardware Feather development boards, HTTP, and the aforementioned modes of data transfer.